Negative pole piece and battery
By using a double-layer coating structure and different ionic polymer electrolytes as binders in the negative electrode sheet, the material dropping and cycle loss problems caused by expansion of the silicon negative electrode battery are solved, and higher flexibility and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510369813.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Existing silicon negative electrode batteries cause large material dropout and circulation losses due to expansion of silicon material. Increasing the amount of adhesive used in traditional methods will lead to increased internal resistance and reduced electrical performance.
The design of a double-layer coated negative electrode sheet is adopted. The first negative electrode active material layer and the second negative electrode active material layer are used as the binder to improve the flexibility and adhesion of the electrode sheet by ionic bond crosslinking.
Effectively inhibit the expansion of silicon-based materials, improve the electrochemical performance of the battery, extend the service life, and reduce internal resistance.
Smart Images

Figure CN119890232A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet and a battery. Background Art
[0002] In recent years, many manufacturers have turned their attention to silicon negative electrode batteries, adding some silicon carbon or silicon oxide to graphite, but the problem they face is the shedding of silicon materials due to the expansion of silicon materials, resulting in large cycle losses. Currently, most companies in the industry use increased amounts of binders to inhibit silicon expansion, but excessive use of binders will increase internal resistance and seriously reduce electrical performance.
[0003] Some companies use new binders. In the patent KR20220122818A of a Korean company, a cross-linked copolymer is used as a silicon negative electrode binder. This cross-linked copolymer is prepared by cross-linking the side chain of polyethylene glycol terminated with a dibenzaldehyde group to the main chain side chain of ethylene glycol chitosan. The imine bond contained in the cross-linked polymer has excellent self-healing ability, adhesion and mechanical strength, and can achieve the same effect without increasing the amount used. However, the groups contained in this type of binder have extremely strong adsorption to graphite or silicon, and the negative electrode slurry will cause abnormal gelation, which is not suitable for mass production.
[0004] Some companies have proposed using a double-layer coating method, placing the silicon-containing slurry on the bottom layer closer to the current collector or the top layer farther away. For example, Tianjin Lishen’s patent CN116230867A uses a double-layer coating process to make SiO x More distributed in the inner layer, using the surface graphite to suppress SiO x The volume expansion of the negative electrode material is improved, and the overall conductivity of the negative electrode material is improved. At the same time, more binders and conductive agents are distributed in the inner layer to increase the bonding force of the composite negative electrode. For example, in the patent CN110148708A of Zhuhai Guanyu, it is proposed that the first coating layer is the bottom graphite coating close to the negative electrode current collector, and the second coating layer is the top silicon-containing coating away from the negative electrode current collector. The double-layer coating technology is used to apply the two slurries to the negative electrode current collector at the same time to obtain a double-layer coated negative electrode sheet with a silicon-containing coating on the top layer and a silicon-free pure graphite layer on the bottom layer. However, simply placing the silicon-containing slurry on the bottom or top layer cannot significantly improve the expansion of the silicon negative electrode, and it increases the difficulty of preparing the electrode sheet. Moreover, because the upper and lower layers of slurry contain different components and different surface tensions, pits are easily formed on the surface of the electrode sheet, resulting in lithium precipitation. Summary of the invention
[0005] In view of this, the present invention provides a negative electrode plate and a battery. The negative electrode plate adopts a double-layer coating method, and the binder contained in the two active material layers is a polymer electrolyte of different ions. The different ionic polymer electrolytes form ionic bonds and cross-links, which can improve the flexibility of the plate, effectively inhibit the expansion of silicon-based materials, and the surface tension of the plate is consistent, which helps to improve the electrochemical performance of the battery.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: In a first aspect, the present invention provides a negative electrode plate, the negative electrode plate comprising: (a) negative electrode current collector; (b) a first negative electrode active material layer, the first negative electrode active material layer is disposed on at least one surface of the negative electrode current collector, and the first negative electrode active material layer includes a first silicon-based material and a first binder; (c) a second negative electrode active material layer, the second negative electrode active material layer is disposed on a surface of the first negative electrode active material layer away from the negative electrode current collector, and the second negative electrode active material layer includes a second silicon-based material and a second binder; The first binder and the second binder are one of the following (i) or (ii): (i) the first binder comprises a cationic polymer electrolyte, and the second binder comprises an anionic polymer electrolyte; (ii) The first binder includes an anionic polymer electrolyte, and the second binder includes a cationic polymer electrolyte.
[0007] In the embodiment of the present invention, the mass percentage of the cationic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m1, and the mass percentage of the anionic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m2, and m1 and m2 satisfy the following relationship: 0≤|m1-m2| / m1≤20%; and / or, 0≤|m1-m2| / m2≤20%; and / or, m1 is 1.8% to 3.0%; And / or, m2 is 1.8% to 3.0%.
[0008] In an embodiment of the present invention, the cationic polymer electrolyte includes at least one of cationic polyacrylamide, polyethyleneimine, cationic polyvinyl alcohol, and polyvinylamide.
[0009] In an embodiment of the present invention, the cationic group of the cationic polyacrylamide includes at least one of an imidazole group, a pyridyl group, and a piperidyl group.
[0010] In a preferred embodiment of the present invention, the first binder includes a cationic polymer electrolyte, the cationic polymer electrolyte includes cationic polyacrylamide, and the cationic group of the cationic polyacrylamide includes an imidazole group.
[0011] In an embodiment of the present invention, the anionic polymer electrolyte includes at least one of anionic epoxy resin, sodium polyacrylate, anionic polyacrylamide, anionic polyvinyl alcohol, and sodium polystyrene sulfonate.
[0012] In an embodiment of the present invention, the anionic group of the anionic epoxy resin includes at least one of a carboxyl group, a phosphoric acid group, and a sulfonic acid group.
[0013] In an embodiment of the present invention, the first negative electrode active material layer further includes a first carbon-based material and a first conductive agent.
[0014] Preferably, the mass ratio of the first carbon-based material, the first silicon-based material, the first binder and the first conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5).
[0015] In an embodiment of the present invention, the second negative electrode active material layer further includes a second carbon-based material and a second conductive agent.
[0016] Preferably, the mass ratio of the second carbon-based material, the second silicon-based material, the second binder and the second conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5).
[0017] Preferably, the ratio of the thickness of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (5-6):(4-5).
[0018] Preferably, the first negative electrode active material layer has a thickness of 70 to 110 μm.
[0019] Preferably, the second negative electrode active material layer has a thickness of 70 to 110 μm.
[0020] In a second aspect, the present invention provides a battery comprising the above-mentioned negative electrode plate.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. The silicon-containing negative electrode sheet of the present invention adopts a double-layer coating method, and the binder contained in the first negative electrode active material layer and the second negative electrode active material layer is a polymer electrolyte of different ions. First, unlike common binders, this type of binder is a high molecular electrolyte (also known as a polymer electrolyte), which can be dissolved in water, ionizes charges after dissolving in water, and has excellent ion-conducting effect; second, before coating, the polymer electrolyte has a soft molecular chain, which can provide a thickening effect after dissolving and stretching in water to prevent the slurry from settling; third, the polymer electrolyte is divided into anionic polymer electrolytes and cationic polymer electrolytes according to the charges ionized in water, and the binder contained in the first negative electrode active material layer and the second negative electrode active material layer is a polymer electrolyte of different ions. After coating, the anionic polymer electrolyte and the cationic polymer electrolyte are tightly combined due to the charge effect, and form ionic bonds and cross-links during the baking process, which give the negative electrode sheet excellent flexibility after drying, effectively inhibit the expansion of silicon-based materials, and help improve the electrochemical performance of the battery.
[0022] 2. When cationic polyacrylamide is selected as the cationic polymer electrolyte, the amide bond of cationic polyacrylamide has both carbonyl and imino groups, which can undergo a reversible chemical reaction when the material is damaged, reform the chemical bonds, and have a self-repairing function, thereby repairing the material, extending its service life, and improving durability and reliability.
[0023] 3. The main materials and proportions used in the upper and lower layers of slurry of the present invention are preferably kept consistent. Only the binder in the upper and lower layers of slurry is changed, so that the surface tension of the electrode is consistent, the surface of the electrode is smooth, and it is not easy to cause lithium deposition, which helps to improve the electrochemical performance of the battery.
[0024] Therefore, the present invention can make the two active material layers have higher adhesion, improve the flexibility of the pole piece, effectively inhibit the expansion of the silicon-based material, have a self-repairing function, and help improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the structure of the negative electrode plate of the present invention.
[0026] The reference numerals are as follows: 1. Negative electrode current collector; 2. a first negative electrode active material layer; 3. Second negative electrode active material layer. DETAILED DESCRIPTION
[0027] The present invention discloses a negative electrode sheet and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0028] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0029] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] Specifically, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a negative electrode plate, the negative electrode plate comprising: (a) negative electrode current collector; (b) a first negative electrode active material layer, the first negative electrode active material layer is disposed on at least one surface of the negative electrode current collector, and the first negative electrode active material layer includes a first silicon-based material and a first binder; (c) a second negative electrode active material layer, the second negative electrode active material layer is disposed on a surface of the first negative electrode active material layer away from the negative electrode current collector, and the second negative electrode active material layer includes a second silicon-based material and a second binder; The first binder and the second binder are one of the following (i) or (ii): (i) the first binder comprises a cationic polymer electrolyte, and the second binder comprises an anionic polymer electrolyte; (ii) The first binder includes an anionic polymer electrolyte, and the second binder includes a cationic polymer electrolyte.
[0035] The silicon-containing negative electrode plate of the present invention adopts a double-layer coating method, and the binder contained in the first negative electrode active material layer and the second negative electrode active material layer is a polymer electrolyte of different ions. First, unlike common binders, this type of binder is a high molecular electrolyte (also known as a polymer electrolyte), which can be dissolved in water, ionizes charges after being dissolved in water, and has excellent ion-conducting effect; second, before coating, the polymer electrolyte has a soft molecular chain, which can provide a thickening effect after being dissolved and stretched in water to prevent the slurry from settling; third, the polymer electrolyte is divided into anionic polymer electrolytes and cationic polymer electrolytes according to the charges ionized in water, and the binder contained in the first negative electrode active material layer and the second negative electrode active material layer is a polymer electrolyte of different ions. After coating, the anionic polymer electrolyte and the cationic polymer electrolyte are tightly combined due to the charge effect, and ionic bonds are formed during the baking process. Cross-linking, after drying, gives the negative electrode plate excellent flexibility, effectively inhibits the expansion of silicon-based materials, and helps to improve the electrochemical performance of the battery.
[0036] In the embodiment of the present invention, the mass percentage of the cationic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m1, and the mass percentage of the anionic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m2, and m1 and m2 satisfy the following relationship: 0≤|m1-m2| / m1≤20%; and / or, 0≤|m1-m2| / m2≤20%; and / or, m1 is 1.8% to 3.0%; And / or, m2 is 1.8% to 3.0%.
[0037] Exemplarily, the value of |m1-m2| / m1 or 0≤|m1-m2| / m2 is any value of 0, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, or any value within the range of any two of the above values. When the value of |m1-m2| / m1 or 0≤|m1-m2| / m2 is greater than 20%, it is easy to cause insufficient combination of cationic polymer electrolyte and anionic polymer electrolyte, so that the flexibility effect is deteriorated.
[0038] In an embodiment of the present invention, m1 is 1.8% to 3.0%. Exemplarily, m1 is any value among 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, or any value within a range of any two of the above values. When m1 is less than 1.8%, too little binder will cause the slurry viscosity to be too thin, resulting in sedimentation; when m1 is greater than 3.0%, the internal resistance will increase and the energy density will be low.
[0039] In an embodiment of the present invention, m2 is 1.8% to 3.0%. Exemplarily, m2 is any value among 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, or any value within a range of any two of the above values. When m2 is less than 1.8%, too little binder will cause the slurry viscosity to be too thin, resulting in sedimentation; when m2 is greater than 3.0%, the internal resistance will increase, and the energy density will be low.
[0040] In an embodiment of the present invention, the cationic polymer electrolyte includes at least one of cationic polyacrylamide, polyethyleneimine, cationic polyvinyl alcohol, and polyvinylamide.
[0041] Preferably, the cationic polymer electrolyte includes cationic polyacrylamide. Compared with other cationic polymer electrolytes, the amide bond of cationic polyacrylamide has both carbonyl and imino groups, which can undergo a reversible chemical reaction when the material is damaged, reform the chemical bond, and have a self-repairing function, thereby repairing the material, having a longer service life, and having better durability and reliability.
[0042] In an embodiment of the present invention, the cationic group of the cationic polyacrylamide includes at least one of an imidazole group, a pyridyl group, and a piperidyl group.
[0043] In a preferred embodiment of the present invention, the first binder includes a cationic polymer electrolyte, the cationic polymer electrolyte includes cationic polyacrylamide, and the cationic group of the cationic polyacrylamide includes an imidazole group. Under the above conditions, the polyacrylamide containing the imidazole group can be present in the first negative electrode active material layer, and the first negative electrode active material layer is close to the negative electrode current collector.
[0044] Preferably, the negative electrode current collector is copper foil.
[0045] In a preferred embodiment of the present invention, the imidazole group is bonded to the copper foil by a coordination bond. The coordination bond bonding mainly depends on the nitrogen atom in the imidazole group, which has an unshared electron pair and can participate in cyclic conjugation, reducing the electron density on the nitrogen atom, so that the hydrogen on the nitrogen atom is easy to leave in the form of hydrogen ions, thereby forming a coordination bond with the copper ion. This combination occurs instantly, generating a conductive thin film layer, which is about 0.2~0.4 μm, and can make the first negative electrode active material layer and the negative electrode current collector copper foil tightly bonded, increase the peeling force, prevent the active material from falling off the negative electrode current collector, and increase the cycle life.
[0046] In a specific embodiment of the present invention, the introduced imidazole group includes 1-(2-methacryloyloxypropyl)-3-decyl imidazole hydrochloride.
[0047] In a specific embodiment of the present invention, the introduction of pyridyl includes 1-(1-pyridine-amide)-ethylene.
[0048] In a specific embodiment of the present invention, the introduction of piperidinyl includes 1-(1-piperidinyl-amide)-ethylene.
[0049] In an embodiment of the present invention, the cationic polymer electrolyte includes a first polymer group, and a cationic group modified on the first polymer group.
[0050] Preferably, the mass ratio of the first polymer group to the cationic group is (1-10): 1. Exemplarily, the mass ratio of the first polymer group to the cationic group is any value of 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value within the range of any two of the above values.
[0051] In an embodiment of the present invention, the monomer for preparing the first polymer group includes at least one of acrylamide, ethyleneimine, vinyl alcohol and vinylamide.
[0052] In an embodiment of the present invention, the anionic polymer electrolyte includes at least one of anionic epoxy resin, sodium polyacrylate, anionic polyacrylamide, anionic polyvinyl alcohol, and sodium polystyrene sulfonate.
[0053] Preferably, the anionic polymer electrolyte includes anionic epoxy resin. Anionic epoxy resin can react with a variety of compounds containing active hydrogen, such as polyacrylamide. Polyacrylamide can provide active functional groups, react with anionic epoxy resin, introduce dynamic polyamide bonds, and make the formed compound have good toughness while maintaining three-dimensional cross-linking; in addition, when the cationic polymer electrolyte uses a cationic polymer electrolyte containing imidazole groups, the imidazole groups can also promote the curing of anionic epoxy resin. Imidazole is a five-membered compound containing two nitrogen atoms, one of which constitutes a secondary amine and the other constitutes a tertiary amine. This structure allows the imidazole groups to be used as a curing agent to quickly cure the anionic epoxy resin, increase the reaction speed, and quickly cure the active material layer.
[0054] In an embodiment of the present invention, the anionic group of the anionic epoxy resin includes at least one of a carboxyl group, a phosphoric acid group, and a sulfonic acid group.
[0055] Preferably, the anionic group of the anionic epoxy resin includes a carboxyl group. The reason why the anionic group of the anionic epoxy resin is preferably a carboxyl group is that the carboxyl group contains a carbonyl group and a hydroxyl group, has a strong polarity, and can interact with the functional groups on the surface of the main material (hydroxyl, carboxyl, carbonyl, keto, etc. For example, the main material includes both carbon-based materials graphite and silicon-based materials. Graphite is a layered crystal with a large number of oxygen-containing functional groups on its surface and interlayer defects. These functional groups form a series of polar groups during the sintering process) to effectively disperse carbon-based materials such as graphite.
[0056] In an embodiment of the present invention, the anionic epoxy resin includes at least one of 2-carboxyl-diphenol propane epoxy resin, 2-phosphoric acid-diphenol propane epoxy resin, and 2-sulfonic acid-diphenol propane epoxy resin.
[0057] In a specific embodiment of the present invention, the substance introducing the carboxyl group comprises lactic acid.
[0058] In a specific embodiment of the present invention, the introducer of phosphate group comprises a nucleotide.
[0059] In a specific embodiment of the present invention, the introducing substance of the sulfonic acid group comprises sulfuric acid.
[0060] In an embodiment of the present invention, the anionic polymer electrolyte includes a second polymer group, and an anionic group modified on the second polymer group.
[0061] Preferably, the molar ratio of the second polymer group to the anionic group is (1-10): 1. Exemplarily, the molar ratio of the second polymer group to the anionic group is any value of 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any value within the range of any two of the above values.
[0062] In an embodiment of the present invention, the second polymer group includes bisphenol A type epoxy resin.
[0063] In an embodiment of the present invention, the first negative electrode active material layer further includes a first carbon-based material and a first conductive agent.
[0064] Preferably, the mass ratio of the first carbon-based material, the first silicon-based material, the first binder and the first conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5). Exemplarily, the mass ratio of the first carbon-based material, the first silicon-based material, the first binder and the first conductive agent is any value among 75:20:1.8:1.5, 85:10:3:0.5, 80:15:2.4:1, 82.5:14.5:2:1, 82.5:14.5:1.8:1.2, 81.5:14.5:3:1 or any value within the range of any two of the above values.
[0065] In an embodiment of the present invention, the second negative electrode active material layer further includes a second carbon-based material and a second conductive agent.
[0066] Preferably, the mass ratio of the second carbon-based material, the second silicon-based material, the second binder and the second conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5). Exemplarily, the mass ratio of the second carbon-based material, the second silicon-based material, the second binder and the second conductive agent is any value among 75:20:1.8:1.5, 85:10:3:0.5, 80:15:2.4:1, 82.5:14.5:2:1, 82.5:14.5:1.8:1.2, 81.5:14.5:3:1 or any value within the range of any two of the above values.
[0067] In a preferred embodiment of the present invention, the main materials and proportions used in the slurry of the first negative electrode active material layer and the second negative electrode active material layer are preferably kept consistent, and only the binder in the upper and lower layers of the slurry is changed. This can make the surface tension of the electrode consistent, make the surface of the electrode smooth, and not easily cause lithium deposition, which helps to improve the electrochemical performance of the battery.
[0068] In an embodiment of the present invention, the first carbon-based material and the second carbon-based material independently include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, and hard carbon.
[0069] In an embodiment of the present invention, the first silicon-based material and the second silicon-based material independently include at least one of elemental silicon, silicon oxygen, silicon carbon, and silicon alloy.
[0070] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.
[0071] Preferably, the ratio of the thickness of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (5-6): (4-5). Exemplarily, the ratio of the thickness of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is any value of 5:5, 5.5:4.5, 6:4, or any value within the range of any two of the above values. When the thickness ratio is not within this range, it will result in different ratios of binders in the first negative electrode active material layer and the second negative electrode active material layer, and poor bonding strength at the interface contact.
[0072] Preferably, the thickness of the first negative electrode active material layer is 70-110 μm. Exemplarily, the thickness of the first negative electrode active material layer is any value among 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, or any value within the range consisting of any two of the above values.
[0073] Preferably, the thickness of the second negative electrode active material layer is 70-110 μm. Exemplarily, the thickness of the second negative electrode active material layer is any value among 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, or any value within the range consisting of any two of the above values.
[0074] In a second aspect, the present invention provides a battery comprising the above-mentioned negative electrode plate.
[0075] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0076] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0077] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0078] The present invention will be further described below in conjunction with embodiments: Embodiment 1: 1. Preparation of negative electrode sheet: (1) Synthesis of imidazole polyacrylamide: Dissolve acrylamide in deionized water, mix thoroughly, and cool to room temperature; inject the solution into a polymer axe, fill with nitrogen, add 1-(2-methacryloyloxypropyl)-3-decyl imidazole hydrochloride as an imidazole introduction agent, and add sodium sulfite as an initiator, control the temperature at room temperature, and perform polymerization reaction. After 10 hours of reaction, a polymer colloid is obtained; the colloid after the reaction is dried, ground and sieved to obtain imidazole polyacrylamide powder. The mass ratio of acrylamide, 1-(2-methacryloyloxypropyl)-3-decyl imidazole hydrochloride, sodium sulfite, and deionized water in the reaction system is 19:5:0.03:76.
[0079] (2) Synthesis of carboxyl epoxy resin: Bisphenol A epoxy resin was selected as the base material, lactic acid as the modifier, and quaternary ammonium salt as the catalyst. The molar ratio of bisphenol A epoxy resin to lactic acid was 5:1, and the ratio of quaternary ammonium salt to the total mass of bisphenol A epoxy resin and lactic acid was 0.2%. After being dissolved in deionized water, the mixture was heated, and the initial temperature was controlled at about 60°C. After 0.5h, the temperature was raised to 100°C and reacted for 3h. After the reaction was completed, the mixture was extracted and dried to obtain a carboxyl epoxy resin.
[0080] (3) Preparation of negative electrode slurry: Graphite, silicon oxide, carbon black (SP), an upper layer binder carboxyl epoxy resin (anionic polymer electrolyte), and deionized water are uniformly mixed at a solid mass ratio of 82.5:14.5:1:2:100 to obtain an upper layer negative electrode slurry; Graphite, silicon oxide, carbon black (SP), lower layer binder imidazole polyacrylamide (cationic polymer electrolyte), and deionized water were evenly mixed at a solid mass ratio of 82.5:14.5:1:2:100 to obtain a lower layer negative electrode slurry.
[0081] (4) Preparation of negative electrode sheet: Using a double-layer die head, the lower negative electrode slurry and the upper negative electrode slurry are simultaneously coated on the surfaces of both sides of the current collector (copper foil). The surface density ratio of the upper and lower slurries is controlled at 5:5. The thickness of the upper and lower coatings is 100 μm. After drying, rolling and die-cutting, the negative electrode sheet is obtained. The schematic diagram of its structure is shown in Figure 1 .
[0082] 2. Preparation of positive electrode sheet: (1) Preparation of positive electrode slurry: Lithium iron phosphate (LFP), carbon black (SP), carbon nanotubes (CNT), polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) were uniformly mixed in a mass ratio of 96:1.5:0.5:2.0:45 to obtain a positive electrode slurry.
[0083] (2) Preparation of positive electrode sheet: The positive electrode slurry is evenly coated on the aluminum foil current collector, and the positive electrode sheet is obtained after drying, rolling and die-cutting.
[0084] 3. Preparation of batteries: The positive electrode sheet, the negative electrode sheet and the separator are wound and assembled in the order of a layer of positive electrode, a layer of separator and a layer of negative electrode. The assembled electrode roll is then encapsulated in an aluminum-plastic film, and the electrolyte is injected into the aluminum-plastic film. The battery is then formed, aged and divided into different sizes. Finally, the aluminum-plastic film is sealed to obtain a battery.
[0085] Embodiment 2: The difference between this embodiment and embodiment 1 is that the upper layer binder is imidazole polyacrylamide (cationic polymer electrolyte), and the lower layer binder is carboxyl epoxy resin (anionic polymer electrolyte).
[0086] Embodiment 3: The difference between this embodiment and embodiment 1 is that the upper layer binder is polyethyleneimine (cationic polymer electrolyte) and the lower layer binder is sodium polyacrylate (anionic polymer electrolyte).
[0087] Embodiment 4: The difference between this embodiment and embodiment 1 is that the proportions of the components in the negative electrode slurry are different.
[0088] Graphite, silicon oxide, carbon black (SP), an upper layer binder carboxyl epoxy resin (anionic polymer electrolyte), and deionized water are uniformly mixed according to a solid mass ratio of 82.5:14.5:1.2:1.8:100 to obtain an upper layer negative electrode slurry; Graphite, silicon oxide, carbon black (SP), lower layer binder imidazole polyacrylamide (cationic polymer electrolyte), and deionized water were evenly mixed at a solid mass ratio of 82.5:14.5:1.2:1.8:100 to obtain a lower layer negative electrode slurry.
[0089] Embodiment 5: The difference between this embodiment and embodiment 1 is that the proportions of the components in the negative electrode slurry are different.
[0090] Graphite, silicon oxide, carbon black (SP), an upper layer binder carboxyl epoxy resin (anionic polymer electrolyte), and deionized water are uniformly mixed at a solid mass ratio of 81.5:14.5:1:3:100 to obtain an upper layer negative electrode slurry; Graphite, silicon oxide, carbon black (SP), lower layer binder imidazole polyacrylamide (cationic polymer electrolyte), and deionized water were evenly mixed at a solid mass ratio of 81.5:14.5:1:3:100 to obtain a lower layer negative electrode slurry.
[0091] Comparative Example 1: The difference between this comparative example and Example 1 is that the formula of the upper and lower negative electrode slurries is consistent, and graphite, silica, carbon black (SP), sodium carboxymethyl cellulose, styrene-butadiene rubber, and deionized water are evenly mixed at a solid mass ratio of 82.5:14.5:1:1:1:100.
[0092] Comparative Example 2: The difference between this comparative example and Example 1 is that the lower layer binder is imidazole polyacrylamide (cationic polymer electrolyte), and the upper layer negative electrode slurry is the same as that in Comparative Example 1.
[0093] Comparative Example 3: The difference between this comparative example and Example 1 is that the upper layer binder is carboxyl epoxy resin (anionic polymer electrolyte), and the lower layer negative electrode slurry is the same as that in Comparative Example 1.
[0094] Comparative Example 4: The difference between this comparative example and Example 1 is that the slurry is not stratified, and graphite, silicon oxide, carbon black (SP), imidazole polyacrylamide (cationic polymer electrolyte), carboxyl epoxy resin (anionic polymer electrolyte), and deionized water are evenly mixed at a solid mass ratio of 82.5:14.5:1:1:1:100.
[0095] Performance Testing: The negative electrode sheets and batteries prepared in the above examples and comparative examples were subjected to the following performance tests: (1) Peeling force: Fix the electrode material area and tear the foil at 90 degrees. The force measured at this time is the peeling force of the electrode.
[0096] (2) Flexibility: Use winding needles of different diameters to curl the electrode and test the minimum diameter when the electrode cracks. The smaller the diameter, the better the flexibility.
[0097] (3) First efficiency (first coulombic efficiency): After the battery is installed, use a constant current of 0.01C to charge to a cut-off voltage of 3.65V, record the charge capacity, and after standing, discharge at 0.33C to 2.5V, record the discharge capacity. The ratio of the first discharge to the charge capacity is the first efficiency.
[0098] (4) Full-charge rebound rate: After the battery is installed, it is charged to a cut-off voltage of 3.65V using a constant current and constant voltage charging method. After disassembly, the thickness of the negative electrode plate is tested. The ratio of the thickness of the negative electrode plate to the thickness of the negative electrode plate after rolling is the full-charge rebound rate.
[0099] (5) Internal resistance: Use a multimeter to clamp the positive and negative terminals of the battery and adjust it to the internal resistance test mode to obtain the internal resistance.
[0100] (6) Cycle number: The battery is repeatedly charged and discharged in a charging 1C and discharging 1C mode. The number of cycles when the capacity retention rate reaches 80% is the cycle number.
[0101] Table 1 By comparing the data of Examples 1-5 with Comparative Example 1, Examples 1-5 have high peeling force, good flexibility, lower full-charge rebound rate and internal resistance, and greatly increased cycle times, which are better than industry standards in all aspects.
[0102] In comparative examples 1-3, the peeling force is relatively low, resulting in a full-charge rebound rate and a number of cycles being worse than those of the embodiments, and the internal resistance is relatively high and the fast-charging capability is relatively poor.
[0103] In Comparative Example 4, because the upper and lower layers are not separated, the anionic polymer electrolyte (carboxyl epoxy resin) and the cationic polymer electrolyte (imidazole polyacrylamide) act prematurely, resulting in the generation of flocs, which reduces the adhesion, and the peeling force and cycle performance are the worst.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: (a) negative electrode current collector; (b) a first negative electrode active material layer, the first negative electrode active material layer being disposed on at least one surface of the negative electrode current collector, the first negative electrode active material layer comprising a first silicon-based material and a first binder; (c) a second negative electrode active material layer, the second negative electrode active material layer being disposed on a surface of the first negative electrode active material layer away from the negative electrode current collector, the second negative electrode active material layer comprising a second silicon-based material and a second binder; The first binder and the second binder are one of the following (i) or (ii): (i) the first binder comprises a cationic polymer electrolyte, and the second binder comprises an anionic polymer electrolyte; (ii) The first binder includes an anionic polymer electrolyte, and the second binder includes a cationic polymer electrolyte.
2. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the cationic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m1, and the mass percentage of the anionic polymer electrolyte in the first negative electrode active material layer or the second negative electrode active material layer is recorded as m2. The m1 and m2 satisfy the following relationship: 0≤|m1-m2| / m1≤20%; and / or, 0≤|m1-m2| / m2≤20%; And / or, the m1 is 1.8% to 3.0%; And / or, the m2 is 1.8% to 3.0%.
3. The negative electrode sheet according to claim 1, characterized in that: The cationic polymer electrolyte includes at least one of cationic polyacrylamide, polyethyleneimine, cationic polyvinyl alcohol and polyvinylamide.
4. The negative electrode sheet according to claim 3, characterized in that: The cationic group of the cationic polyacrylamide includes at least one of an imidazole group, a pyridyl group and a piperidyl group.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The first binder includes a cationic polymer electrolyte, the cationic polymer electrolyte includes cationic polyacrylamide, and the cationic group of the cationic polyacrylamide includes an imidazole group.
6. The negative electrode sheet according to claim 1, characterized in that: The anionic polymer electrolyte includes at least one of anionic epoxy resin, sodium polyacrylate, anionic polyacrylamide, anionic polyvinyl alcohol, and sodium polystyrene sulfonate.
7. The negative electrode sheet according to claim 6, characterized in that: The anionic group of the anionic epoxy resin includes at least one of a carboxyl group, a phosphoric acid group, and a sulfonic acid group.
8. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material layer further includes a first carbon-based material and a first conductive agent; The mass ratio of the first carbon-based material, the first silicon-based material, the first binder and the first conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5); And / or, the second negative electrode active material layer further includes a second carbon-based material and a second conductive agent; The mass ratio of the second carbon-based material, the second silicon-based material, the second binder and the second conductive agent is (75-85): (10-20): (1.8-3): (0.5-1.5).
9. The negative electrode sheet according to claim 1, characterized in that: The ratio of the thickness of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (5-6): (4-5); and / or, the thickness of the first negative electrode active material layer is 70 to 110 μm; And / or, the thickness of the second negative electrode active material layer is 70 to 110 μm.
10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Negative plate and lithium ion battery
CN110148708A
Modified lithium battery negative electrode as well as preparation method and application thereof
CN113991060A
Electrochemical device and electronic device
CN117613355A
Lithium ion secondary battery
JP2018181816A
Negative electrode for secondary battery and secondary battery including the negative electrode
US20150243997A1